Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/ece3.2155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a protection gradient on carnivore density and survival: an example with leopards in the Luangwa valley, Zambia

Abstract: Human activities on the periphery of protected areas can limit carnivore populations, but measurements of the strength of such effects are limited, largely due to difficulties of obtaining precise data on population density and survival. We measured how density and survival rates of a previously unstudied leopard population varied across a gradient of protection and evaluated which anthropogenic activities accounted for observed patterns. Insights into this generalist's response to human encroachment are likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 53 publications
6
69
1
Order By: Relevance
“…, Rosenblatt et al. , ), and prey depletion within the national park itself is notable in this case. Depletion of large herbivores in KNP is linked to long‐term illegal bushmeat poaching at unsustainable levels (Overton et al.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…, Rosenblatt et al. , ), and prey depletion within the national park itself is notable in this case. Depletion of large herbivores in KNP is linked to long‐term illegal bushmeat poaching at unsustainable levels (Overton et al.…”
Section: Discussionmentioning
confidence: 61%
“…, , Rosenblatt et al. ). In KNP, a comparison of carnivore diets now and 50 yr ago showed that the importance of relatively abundant smaller‐bodied herbivores has increased, whereas the importance of larger‐bodied herbivores has decreased (Creel et al.…”
Section: Discussionmentioning
confidence: 99%
“…Poaching and displacement by livestock are known factors contributing to prey depletion (Ripple et al ., ), which can be even more detrimental to carnivores than direct anthropogenic mortality (Rosenblatt et al ., ). These effects can alter lion populations (Henschel et al ., ), and are likely limiting lion occurrence in the village lands.…”
Section: Discussionmentioning
confidence: 97%
“…Although many African ecosystems have maintained all of their large carnivores, the lion Panthera leo , leopard Panthera pardus , cheetah Acinonyx jubatus , and African wild dog Lycaon pictus are all considered vulnerable or endangered, and all show decreasing population trends (IUCN, ). Threats to these carnivores vary among species and populations, but common problems include habitat loss and human encroachment on protected areas (Riggio et al., ; Ripple et al., ; Watson, Becker, Milanzi, & Nyirenda, ), legal and illegal direct killing (Becker et al., ; Creel et al., ; Hofer, Campbell, East, & Huish, ; Ogada, Woodroffe, Oguge, & Frank, ; Packer et al., ; Whitman, Starfield, Quadling, & Packer, ), and prey depletion (Estes et al., ; Fa & Brown, ; Ripple et al., ; Rosenblatt et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-recognized that depletion of prey populations is occurring in many ecosystems, mainly due to habitat loss and illegal harvest (Bolger, Newmark, Morrison, & Doak, 2008;Fa & Brown, 2009;Ripple et al, 2015;Western, Russell, & Cuthill, 2009), and a recent review found that 65% of large carnivores have experienced an increase in the proportion of their prey that is considered vulnerable, threatened, or endangered (Wolf & Ripple, 2016). In short, it is widely recognized that prey depletion can be a strong driver of carnivore declines (Fuller & Sievert, 2001;Karanth & Stith, 1999;Midlane, 2014;Ripple et al, 2015;Rosenblatt et al, 2016). Despite this recognition, there has been little direct research on the manner in which prey depletion alters the diets of large carnivores.…”
Section: Introductionmentioning
confidence: 99%